Improving the Delivery of SOD1 Antisense Oligonucleotides to Motor Neurons Using Calcium Phosphate-Lipid Nanoparticles - Chen, Liyu; Watson, Clare; Morsch, Marco; Cole, Nicholas J.; Chung, Roger S.; Saunders, Darren N.; Yerbury, Justin J.; Vine, Kara L. (Frontiers in Neuroscience, 2017)
Amyotrophic Lateral Sclerosis (ALS) is a fatal neurodegenerative disease affecting the upper and lower motor neurons in the motor cortex and spinal cord. Abnormal accumulation of mutant superoxide dismutase I (SOD1) in motor neurons is a pathological hallmark of some forms of the disease. We have shown that the orderly progression of the disease may be explained by misfolded SOD1 cell-to-cell propagation, which is reliant upon its active endogenous synthesis. Reducing the levels of SOD1 is therefore a promising therapeutic approach. Antisense oligonucleotides (ASOs) can efficiently silence proteins with gain-of-function mutations. However, naked ASOs have a short circulation half-life and are unable to cross the blood brain barrier warranting the use of a drug carrier for effective delivery. In this study, calcium phosphate lipid coated nanoparticles (CaP-lipid NPs) were developed for delivery of SOD1 ASO to motor neurons. The most promising nanoparticle formulation (Ca/P ratio of 100:1), had a uniform spherical core–shell morphology with an average size of 30 nm and surface charge (ζ-potential) of −4.86 mV. The encapsulation efficiency of ASO was 48% and stability studies found the particle to be stable over a period of 20 days. In vitro experiments demonstrated that the negatively charged ASO-loaded CaP-lipid NPs could effectively deliver SOD1-targeted ASO into a mouse motor neuron-like cell line (NSC-34) through endocytosis and significantly down-regulated SOD1 expression in HEK293 cells. The CaP-lipid NPs exhibited a pH-dependant dissociation, suggesting that that the acidification of lysosomes is the likely mechanism responsible for facilitating intracellular ASO release. To demonstrate tissue specific delivery and localization of these NPs we performed in vivo microinjections into zebrafish. Successful delivery of these NPs was confirmed for the zebrafish brain, the blood stream and the spinal cord. These results suggest that CaP-lipid NPs could be an effective and safe delivery system for the improved delivery of SOD1 ASOs to motor neurons. Further in vivo evaluation in transgenic mouse models of SOD1 ALS are therefore warranted.